2023
DOI: 10.22158/jbtp.v11n2p28
|View full text |Cite
|
Sign up to set email alerts
|

A Discussion about the Impact of ChatGPT in Education: Benefits and Concerns

Abstract: The advent of advanced machine learning models such as ChatGPT has led to significant advancements in various fields, including education. The purpose of this article is to explore the impact of ChatGPT in higher education, covering both positive and negative nuances. A critical literature review analysis was conducted, which included references from reliable sources. The methodology used in this article was based on a critical literature review method. The results of the analysis indicate that ChatGPT might h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Moreover, AI applications like ChatGPT are suitable for students across all disciplines, including humanities and social sciences [4,28]. These applications encompass a wide array of functionalities, including language translation, enhanced access to information, the summarization of relevant content tailored to individual queries, question-answering capabilities, support for teaching practices, the facilitation of research tasks such as data analysis and interpretation, and guidance on data collection methods [34,36].…”
Section: Students' Use Of Ai For Academic Purposesmentioning
confidence: 99%
“…Moreover, AI applications like ChatGPT are suitable for students across all disciplines, including humanities and social sciences [4,28]. These applications encompass a wide array of functionalities, including language translation, enhanced access to information, the summarization of relevant content tailored to individual queries, question-answering capabilities, support for teaching practices, the facilitation of research tasks such as data analysis and interpretation, and guidance on data collection methods [34,36].…”
Section: Students' Use Of Ai For Academic Purposesmentioning
confidence: 99%
“…From the review of the studies, one of the areas of interest was the analysis of the missing components of critical thinking. According to de Castro (2023), such components include: reduced analytical thinking, limited possibilities for problem-addressing, lack of diverse perspectives, incomplete understanding of how decisions are made, and reduced metacognition and replication. On reduced analytical thinking, studies revealed that ChatGPT offers quick responses and justifications, which can deter students from using their analytical thinking skills to the fullest.…”
Section: Missing Components Of Critical Thinking Due To Student Use O...mentioning
confidence: 99%
“…Although ChatGPT can help by providing solutions, it might not sufficiently push students to participate in active problem-solving techniques. Students may not fully develop their problem-solving abilities if they are not given chances to think critically and work independently on difficult challenges ( de Castro, 2023). Another missing component of critical thinking is lack of diverse perspectives.…”
Section: Missing Components Of Critical Thinking Due To Student Use O...mentioning
confidence: 99%
See 1 more Smart Citation
“…But like with any new technology, there are also possible drawbacks to take into account. (Castro, 2023).…”
Section: Introductionmentioning
confidence: 99%